An experimental study on carbon fiber thickness and layer thickness of depositing material in fused deposition modeling. (2021) - Sharma, Purushottam; Dhanopia, Ajay Kumar; Joshi, Dheeraj
Abstract: The paper deals with analyses of results of a study on the effect of process parameters in fusion deposition modeling (FDM) 3D printing of a selected composite. Physical models of polylactic acid (PLA) and polylactic acid- carbon fiber (PLA-CF) composites are rapid prototyped through layer by layer deposition (Fusion deposition modeling) technique. Two important process parameters viz. layer thickness of depositing material and thickness of carbon fiber (CF) were optimized to achieve the best set of mechanical properties. Further, tensile strength and flexural strength of the products so fabricated are chosen as response variables so as to study the effects of process parameters on mechanical properties by the use of analysis of variance (ANOVA) technique. The experimental results revealed that the addition of increasing thickness of carbon fiber (CF) in polylactic acid (PLA) based composite raises the tensile strength over that of the pure PLA specimen. Moreover, the tensile strength was found to decrease with an increase in layer thickness of depositing material in CF-PLA composite. The study further revealed that mean flexural strength increases with increasing layer thickness, but, its dependence on CF thickness does not show any specific trend.